Таксономічний статус Pinus kochiаna Klotzsch. еx Koch з Гірського Криму за даними порівняльних популяційно-генетичних досліджень з Pinus sylvestris L. - Коршиков, І.І.; Подгорний, Д.Ю.; Калафат, Л.О.; Пірко, Я.В. (Український ботанічний журнал, 2011)
Изучены генетическое сходство и различия по 20 аллозимным локусам четырех популяций Pinus kochiana Klotzsch. ex Koch Горного Крыма и 18 популяций Pinus sylvestris L. степной и лесостепной зон, Полесья, Расточья и Украинских Карпат. Установлено, что по коэффициенту генетической дистанции Нея популяции P. kochiana наиболее отличаются от реликтовых популяций P. sylvestris Украинских Карпат (DN = 0,021). Однако популяционно-генетические отличия между P. kochiana и P. sylvestris не превышают уровня межпопуляционной изменчивости P. sylvestris, что ставит под сомнение видовой статус P. kochiana. The genetic similarities and differences using 20 allozyme loci have been studied in four populations of Pinus kochiana Klotzsch. ex Koch from Mountain Crimea and 18 populations of Pinus sylvestris L. from steppe and forest-steppe zones, Polesie, Roztochiye, and the Ukrainian Carpathians. It has been determined that the coefficient of Nei’s genetic distance of the populations of P. kochiana most different from the relict populations of P. sylvestris from the Ukrainian Carpathians (DN = 0,021). However population and genetic differences between P. kochiana and P. sylvestris does not go beyond the interpopulational variation of P. sylvestris, which calls into question the species status of P. kochiana.